SPECTROSCOPIC STUDY OF THE HOT SUPERGIANT zeta PERSEI - Butkovskaya, V. V.; Baklanova, D. N.; Plachinda, S. I. (Одеські астрономічні публікації, 2010)
The preliminary results of the high-resolution spectroscopic study of the hot supergiant ζ Persei (B1 Ib) are presented. It was found that the radial velocity of ζ Persei measured in the He I 6678Å line varies from night to night probably in the α Cygni manner.